The labour recruitment of local inhabitants as Rōmusha in japanese-occupied South East Asia - Melber, Takuma (International review of social history. Special issue, 2016)
During World War II, Japan, as occupying power, mobilized thousands of labourers in South East Asia. While the history of Allied prisoners of war (POWs) deployed as forced labourers on the Burma-Siam “Death Railway” is well known, the coercive labour recruitment of local inhabitants as so-called rōmusha has, until today, remained an almost completely untold story. This article introduces rōmusha, with a particular focus on the Burma-Siam Railway, and presents the methods used by the occupying powers to recruit local inhabitants in Java, Malaya, and Singapore, initially as volunteers, and increasingly using force. We look, too, at the tactics and strategies of avoidance the locals were able to deploy. The article offers insights into the poor working conditions on the railway, discusses the body count, and gives an idea of the huge impact of the forced labour recruitment not only in economic terms, but also in terms of the effect it had on the social structure at both the micro and macro levels.